2014
DOI: 10.1111/maec.12117
|View full text |Cite
|
Sign up to set email alerts
|

Skin toxins in coral‐associated Gobiodon species (Teleostei: Gobiidae) affect predator preference and prey survival

Abstract: Predation risk is high for the many small coral reef fishes, requiring successful sheltering or other predator defence mechanisms. Coral-dwelling gobies of the genus Gobiodon live in close association with scleractinian corals of the genus Acropora. Earlier studies indicated that the low movement frequency of adult fishes and the development of skin toxins (crinotoxicity) are predation avoidance mechanisms. Although past experiments showed that predators refuse food prepared with goby skin mucus, direct predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Neoverrucotoxin in fish venom has a mechanism of action where it has been shown to function by forming pores in cell membranes [ 37 ]. The skin toxins in Gobiodon have a range of biological functions, including parasite and predator prevention [ 38 ]. The upregulation of the neoverrucotoxin subunit beta protein was likely to defend fish against the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Neoverrucotoxin in fish venom has a mechanism of action where it has been shown to function by forming pores in cell membranes [ 37 ]. The skin toxins in Gobiodon have a range of biological functions, including parasite and predator prevention [ 38 ]. The upregulation of the neoverrucotoxin subunit beta protein was likely to defend fish against the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, some Elacatinus or Gobiodon gobies can secrete toxic compounds from their skins that appear to be noxious to predators (Colin, 1975;Schubert et al, 2003). As a consequence, predators exhibit comparably low preference for these gobies (Colin, 1975;Schubert et al, 2003;Gratzer et al, 2015). As a consequence of investing into predator defence, the life-history strategies of these gobies may deviate from the short lifespan and high mortality typical of other CRF species (Miller, 1996).…”
Section: (B) Survivalmentioning
confidence: 99%
“…Goby epidermal toxins and their ecological implications are well studied and provide a good example of the importance and complexity of fish mucus molecules in ecosystem dynamics. Coral gobies are known to possess different epidermal mucus toxins that exhibit predator deterrence and parasite avoidance [66,161]. Recent studies have shown how goby mucus substances play a key role in the mutualistic association between gobies and corals [162,163].…”
Section: Interspecific Communicationmentioning
confidence: 99%
“…Acropora corals use chemicals to attract gobies when attacked by toxic seaweeds, and in turn, gobies trim the seaweed and increase their own mucus toxicity, protecting them against predators and parasites [163]. At the same time, goby skin mucus repels corallivores, protecting corals from predation [161]. However, even though the ecological role of goby epidermal mucus toxins is well studied, their chemical structures are still unknown.…”
Section: Interspecific Communicationmentioning
confidence: 99%